Evaluasi Penggunaan Aplikasi TIX ID Dengan Menggunakan Metode - Damayanti, Murni (Jurnal Inovatif, 2023)
KEYWORDS: ABSTRACT TIX ID, User Evaluation, Usability Testing TIX ID, a popular app in Indonesia, enables affordable movie ticket purchases. It collaborates with DANA for faster payments. This research evaluates TIX ID's features, user experience, and satisfaction. The study employed online surveys, observations, interviews, and Usability Testing. Findings indicate TIX ID facilitates online ticket purchases, but navigation and app stability needs improvement. This research significantly contributes to understanding TIX ID's usability, guiding further enhancements to increase user satisfaction and effectiveness. Overall, the research shows TIX ID considers usability factors. Respondents reported average scores of 4.30 for Learnability, 4.28 for Efficiency, 4.15 for Memorability, 3.36 for Errors, and 4.21 for Satisfaction. However, attention is needed, especially regarding Errors. Occasional issues occur during booking and payment processes in the TIX ID app. This should prompt the development team to seek appropriate solutions, ensuring a comfortable user experience free from previous problems. KATA KUNCI: ABSTRAK TIX ID, Evaluasi Pengguna, Usability Testing TIX ID adalah aplikasi populer di Indonesia yang memudahkan pembelian tiket bioskop dengan harga terjangkau. Aplikasi ini bekerja sama dengan DANA untuk pembayaran yang lebih cepat. Penelitian ini mengevaluasi fitur, pengalaman, dan kepuasan pengguna TIX ID. Metode penelitian meliputi survei online, observasi, wawancara, dan Usability Testing. Hasil penelitian menunjukkan TIX ID memudahkan pembelian tiket online, tetapi perlu perbaikan navigasi dan stabilitas aplikasi. Penelitian ini memberikan kontribusi penting dalam memahami usability TIX ID untuk perbaikan dan pengembangan selanjutnya. Skor rata-rata pengujian menunjukkan TIX ID memiliki Learnability 4,30, Efisiensi 4,28, Memorabilitas 4,15, Errors 3,36, dan Statisfaction 4,21. Namun, terdapat masalah pada Errors saat pemesanan dan pembayaran yang perlu dicari solusinya.)